Economic optimization of insulation and grounding in AC transmission line exposed to direct lightning strokes (2019)
"In this document, De Oliveira/Hileman economic optimization model was applied in the same EPRI's 345kV HVAC line using four different BFR techniques such as EPRI Red Book, IEEE 1247 (Flash program), CIGRE and Montecarlo-ATP. Resulting marginal and total cost curves of the BFR are evaluated and compared. Furthermore, the economic method was also applied to a real-world transmission line located in Colombia (Colectora 1 - Cuestecitas - La Loma 500kV). The method allows to determine marginal cost of the BFR either for the EPRI test case (345kV) or the Colombian test case (500kV)."--Tomado del Formato de Documento de Grado.